The Socio-economic Factors Impacting Juvenile Delinquency: An Exploratory Study - Riya Das; Md Sajidul Huq (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
This study investigates the socio-economic determinants of juvenile delinquency in Bangladesh, focusing on juveniles documented in police reports in Dhaka. The purpose of the research is to examine how family instability, parental neglect, peer influence, neighborhood insecurity, and financial deprivation contribute to delinquent behavior. A mixed-methods design was adopted, combining structured surveys of 100 juveniles housed in Juvenile Development Centers with in-depth interviews of law enforcement officers, psychologists, and social workers, alongside case study analysis of police records. Results show that 81% of offenders belonged to the 16–18 age group, with 70% being male and 30% female. Educational deprivation was widespread, with 82% having no or only primary-level education. Household income data revealed that 83% came from low to lower-middle- income families, while 76% of parents lacked formal education. Peer influence emerged as a decisive factor, with 83% of juveniles admitting involvement in delinquent activities under the influence of friends. Regression and correlation analyses confirmed significant associations between family structure, income, peer networks, and drug use, while case studies revealed organized recruitment of youth by criminal gangs and political exploitation. The findings underline that juvenile delinquency is not only a matter of individual deviance but also a structural problem linked to socio-economic deprivation and institutional weakness. The practical value of this research lies in its recommendations to strengthen family welfare programs, expand vocational training, improve enforcement of the Children Act 2013, and develop integrated rehabilitation systems aimed at reducing recidivism and promoting safer communities.